Haunting license - Perry, Carol J. (Perry, Carol J. Haunted Haven mystery, 2024)
"It's June in Haven, Florida, a "between seasons" time in the tourism business, and Maureen's Haven House Inn is feeling the pinch. There are plenty of ghosts in residence, but Maureen needs living guests to pay the bills. Inspired by an old brochure she finds in a trunk she inherited along with the inn from her mysterious benefactor Penelope Josephine Gray, she gets the brilliant idea to revive a June fishing tournament from twenty years ago, hoping to reel in anglers who'd love to catch the Gulf Coast's popular kingfish and take home a trophy. But one fisherman won't make it to the tournament. While walking on the beach with her golden retriever Finn, Maureen discovers a body. When Officer Frank Hubbard arrives, he recognizes local charter boat fisherman Eddie Manuel. Now it's up to Maureen and her spirited sleuths to sort through the red herrings and bait a hook for a killer before someone else ends up sleeping with the fishes...--